Georg Friedrich Knapp and Modern Monetary Theory - Jan Greitens (Wirtschaftsdienst)
Abstract Knapp’s “State Theory of Money” (1905) claims that “Money is an entity of the legal order.” Money is a chartal means of payment, the value of which is independent of the metal value. Money is regulated by the modern state, but this could also be done by non-governmental communities. Contemporary criticism of Knapp reads like criticism of MMT: The danger of inflation is not taken seriously, there is an overreliance on the state, and the approach is too narrowly focused on the monetary side of the economy. MMT’s reception of Knapp suffers from the abbreviated translation into English. Politically, Knapp calls for austerity policies. Therefore, MMT is only loosely rooted in Knapp.